Advances in binary nitride coatings for cemented carbides. Issue 1 (1st April 2022) - Wang, Xinwu; Sun, Haobin; Zhang, Hua; Li, Changye; Zhao, Chengliang; Si, Shouji; Yao, Haibin; Yu, Huijun; Chen, Chuanzhong
Abstract: With the development of science and technology, cemented carbide tool coatings for machining are updating constantly. Different chemical elements in tool coatings have different performance. This paper introduces the current status of the use of various chemical elements in carbide tool coatings, common chemical elements include metallic elements (transition metal elements, rare-earth elements and aluminium elements) and non-metallic elements (silicon and boron). In addition, this paper presents the current status of research on related basic coatings which includes CrN, TiN, TiCN and CrCN coating, and it looks ahead the develop of tool coating prospect as well.